1999
DOI: 10.1046/j.1365-2842.1999.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the development of dental erosion in vitro: enamel type, temperature and exposure time

Abstract: The influence of temperature, duration of exposure, and enamel type on the development and progression of dental erosion has been determined. Three experiments were devised as follows. Eroded lesions were produced on enamel samples with orange juice: (1) at different temperatures; (2) for different lengths of time; and (3) on bovine permanent, human deciduous and human permanent enamel. Lesion parameters (mineral loss and lesion depth) were quantified using transverse microradiography. Both lesion parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
2
32

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 23 publications
6
112
2
32
Order By: Relevance
“…This result corroborates previous observations by Meurman and Frank (9), who did not find any noticeable morphological difference between eroded enamel specimens originated from cattle or human beings. On the other hand, the present finding is inconsistent with the results of an in vitro study in which progression of erosive lesions in bovine enamel was observed to occur twice faster (10). This may be ascribed to the fact that although bovine enamel may have been more susceptible to demineralization due to its wider interprismatic region, intraorally this structural difference may not have played a role.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result corroborates previous observations by Meurman and Frank (9), who did not find any noticeable morphological difference between eroded enamel specimens originated from cattle or human beings. On the other hand, the present finding is inconsistent with the results of an in vitro study in which progression of erosive lesions in bovine enamel was observed to occur twice faster (10). This may be ascribed to the fact that although bovine enamel may have been more susceptible to demineralization due to its wider interprismatic region, intraorally this structural difference may not have played a role.…”
Section: Discussioncontrasting
confidence: 99%
“…While in an in vitro study (9) surface ultrastructure of bovine and human enamel following erosive episodes was indistinguishable, in another investigation eroded lesions have been shown to progress twice as fast in bovine than in human enamel (10). As a result, enamel originated from cattle has been suggested to wear more than human enamel under laboratory conditions (11).…”
Section: Viability Of Using Enamel and Dentin From Bovine Origin As Amentioning
confidence: 97%
“…Although it is a weak acid, citric acid chelates calcium from hydroxyapatite 18 and promotes the dissolution of crystals by binding the hydrogen ion to the carbonate and/or phosphate ion. 22 Although the manufacturer does not mention the presence of acidulants (e.g., citric acid) or any other acids, fermented milk (Yakult ® ) has a pH of 3.67 and may cause superficial mineral loss in bovine surface enamel after 20 min of exposure, interspersed with exposure to artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the initial microhardness test, the specimens were immersed in artificial saliva as described by McKnight-Hanes and Whitford 17 and modified according to Amaechi et al 18 for 24 h at 37ºC.…”
Section: Selection Of Teeth and Preparation Of Specimensmentioning
confidence: 99%
“…Fragments were flatenned, polished and fixed in resin blocks. Two piece of tapes were placed on the surface, leaving an exposed area 3x1mm 2 . For the formation of erosion lesions, specimens were submitted to an acid challenge by 4 cycles of 2 minutes each, with 0.01 M hydrochloric acid solution (pH 2).…”
mentioning
confidence: 99%